Automatic Detection of Foot Arch Using Clarke's Angle Calculation Through A Web-Integrated System for Children - Shobiha Awwaliyah; Rivantona, Qalbi; Pahlevi, Alfaturachman Maulana; Nurcipto, Dedi; Kurniatie, Menik Dwi (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Foot deformities, particularly flatfeet (pes planus), are frequently observed in children. Although many children exhibit some form of flatfeet, this condition can persist and cause biomechanical issues, pain, and postural misalignments. Early detection and monitoring of foot arch development are critical to preventing long-term complications. However, common diagnostic methods such as wet foot print tests, X-rays, and MRIs are costly, time-consuming, and involve radiation exposure. This study proposes an innovative web-based system that detects foot arch types in children using Clarke’s Angle. The system employs digital image processing to calculate the arch angle, offering a non-invasive, efficient, and cost-effective alternative to existing methods. The system was tested on 180 children aged 2-7 years at two locations in Semarang: Kindergarten & Daycare Habibie Ainun Tlogosari and Integrated Service Post Kemuning. The results from the Clarke’s Angle measurements from the web-based system were compared with the wet foot print test, showing minimal differences and achieving an accuracy rate of 98.89%. This system offers a reliable solution for early detection and is suitable for use in both clinical and community health settings. It provides a faster, more accessible approach to pediatric foot assessment, delivering real-time results and eliminating any waiting time.